Jurassic to Lower Cretaceous tectonostratigraphy of the German Central Graben, southern North Sea. (9th March 2023) - Müller, Simon Maximilian; Jähne-Klingberg, Fabian; Thöle, Hauke; Jakobsen, Finn Christian; Bense, Frithjof; Winsemann, Jutta; Gaedicke, Christoph
Abstract: The Central Graben is a Mesozoic sedimentary basin that is significantly influenced by rift and salt tectonics. Its southern part is located in the German and Dutch sectors of the North Sea. Even though studies exist on the tectonic and stratigraphic development of the Danish and Dutch Central Graben, the German Central Graben as an important link is less investigated. We aim to fill this gap and to investigate the sedimentary development from the Latest Triassic to the Early Cretaceous, the relative influence of salt and rift tectonics on subsidence and how our results fit into the existing studies of the Danish and Dutch Central Graben. Knowledge of the development of the graben and its sedimentation is critical for any possible economic use like hydrocarbon exploitation or carbon capture and storage. Therefore, we mapped nine laterally traceable horizons on 2D and 3D reflection seismic data from the Lower Jurassic to the Lower Cretaceous within the German Central Graben and adjacent Danish Salt Dome Province as well as the northern Dutch Central Graben. These horizons include the base horizons of four tectonostratigraphic mega-sequences of the southern Central Graben adopted from the current Dutch tectonostratigraphic concept. Based on the mapping results, we constructed subsidence, thickness and erosion maps of the tectonostratigraphic mega-sequences and their subdivisions. The tectonostratigraphic mega-sequences were then correlated with well logs to determine the lithology. The results show that the structural and stratigraphic architecture of the German Central Graben was consecutively dominated by either subsidence controlled by rifting, salt tectonics or by thermal uplift and subsidence. We suggest that the German Central Graben is divided by a large strike-slip fault zone, the Mid Central Graben Transverse Zone, into a northern part that geologically rather belongs to the Danish and a southern part that rather belongs to the Dutch Central Graben. We discuss how this division and the tectonics influenced the regional lithology.